1999
DOI: 10.1007/s100670050125
|View full text |Cite
|
Sign up to set email alerts
|

Decreased CD4+ Lymphocyte Activation and Increased Interleukin-4 Production in Peripheral Blood of Rheumatoid Arthritis Patients After Acute Starvation

Abstract: We investigated the effects of acute starvation on mitogen-induced T-cell activation and Th1/Th2 cytokine responses in rheumatoid arthritis (RA) patients. Ten RA patients with active disease underwent a 7-day fast followed by a 2-week refeeding period. Immunological, hormonal, laboratory and clinical evaluations were carried out on days 0, 7 and 21. Using flow cytometry, mitogen-stimulated T-cell activation was assessed in fresh heparinised blood via analysis of CD69 expression. Production of Th1 (interferon-g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
81
2
4

Year Published

2009
2009
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 132 publications
(89 citation statements)
references
References 29 publications
2
81
2
4
Order By: Relevance
“…70,71 In these subjects, it has been reported that acute fasting induces an improvement of different clinical and biological measures of disease activity associated with a fall in circulating leptin, which is related to CD4 lymphocyte hyporeactivity and increased IL-4 secretion. 72 However, the same investigators showed that after a 7-day ketogenic diet in patients with RA, there were no significant changes in any clinical or biological measurements of disease activity, despite a significant increase in serum leptin concentrations. 57,72 Serum levels of leptin have generally been reported to be higher in patients with RA than in control subjects.…”
Section: Leptin and Autoimmunity M Vadacca Et Al 207mentioning
confidence: 96%
See 1 more Smart Citation
“…70,71 In these subjects, it has been reported that acute fasting induces an improvement of different clinical and biological measures of disease activity associated with a fall in circulating leptin, which is related to CD4 lymphocyte hyporeactivity and increased IL-4 secretion. 72 However, the same investigators showed that after a 7-day ketogenic diet in patients with RA, there were no significant changes in any clinical or biological measurements of disease activity, despite a significant increase in serum leptin concentrations. 57,72 Serum levels of leptin have generally been reported to be higher in patients with RA than in control subjects.…”
Section: Leptin and Autoimmunity M Vadacca Et Al 207mentioning
confidence: 96%
“…72 However, the same investigators showed that after a 7-day ketogenic diet in patients with RA, there were no significant changes in any clinical or biological measurements of disease activity, despite a significant increase in serum leptin concentrations. 57,72 Serum levels of leptin have generally been reported to be higher in patients with RA than in control subjects. 70,71,73 Bokarewa et al also observed that circulating plasma concentrations of leptin were significantly higher than matched synovial fluid sample leptin levels.…”
Section: Leptin and Autoimmunity M Vadacca Et Al 207mentioning
confidence: 96%
“…In patients with RA, circulating leptin levels have been described as higher or unmodified in comparison with healthy controls (Bokarewa et al 2003, Otero et al 2006. In RA patients, a food restriction-induced decrease in circulating leptin is associated with CD4C lymphocyte hyporeactivity and increased IL 4 secretion (Fraser et al 1999). Experimental antigen-induced arthritis is less severe in ob/ob mice than in WT littermate, whereas ob/ob and db/db mice exhibited a delayed resolution of inflammatory process in zymosan-induced experimental arthritis.…”
Section: Leptin: a Mediator Of Immuno-inflammatory Responsementioning
confidence: 99%
“…The most important reason is likely a reduction in arachidonic acid (AA) intake, resulting in a lower production of inflammatory eicosanoids. During the fasting state, a reduction in the activation of TCD4 cells and an increase in the number and/or function of the anti-inflammatory cytokine interleukin 4 have been observed; Calorie restriction leads to a reduction in oxidative stress (Fraser et al, 1999;Wolters, 2005). However, the few studies that have addressed the effect of caloric restriction on psoriasis offer inconsistent data on the benefits of this conduct over a long period of time (Lithell et al, 1983;Rucevic et al, 2003).…”
Section: Influence Of Calorie Intake Periods Of Fasting and Vegetarimentioning
confidence: 99%